The ColRS-Regulated Membrane Protein Gene XAC1347 Is Involved in Copper Homeostasis and hrp Gene Expression in Xanthomonas citri subsp. citri - Fan, Xiaojing; Guo, Jing; Zhou, Yinghui; Zhuo, Tao; Hu, Xun; Zou, Huasong (Frontiers in Microbiology, 2018)
Xanthomonas citri subsp. citri (Xcc) is the major causal agent of citrus canker disease. The XAC1347 gene, which encodes a conserved membrane protein in Xcc, is required for virulence during infection. However, the molecular events mediated by XAC1347 remain unclear. In this study, we reported that XAC1347 gene is positively regulated by two component regulatory system ColRS and required for type III secretion system function. A non-polar deletion mutant of the XAC1347 gene resulted in a Hrp minus phenotype in plants and reduced copper homeostasis. Real-time PCR experiments indicated that XAC1347 gene is induced by copper ions. The expression levels of representative genes from four hrp operons, including hrpB1, hrcV, hrpF and hrpD6, were reduced in XAC1347 mutant, indicating that XAC1347 is involved hrp gene expression.